2023
DOI: 10.1111/mve.12639
|View full text |Cite
|
Sign up to set email alerts
|

Vector‐borne protozoan and bacterial pathogen occurrence and diversity in ectoparasites of the Egyptian Rousette bat

Abstract: Bats are known reservoir hosts for a wide variety of parasites and pathogens, including bacteria and protozoans. Some of these pathogens are vector‐borne, and although their role is poorly studied, ectoparasites may contribute significantly to their transmission. The aim of this study was to molecularly detect the presence of vector‐borne microorganisms in bat‐associated ectoparasites to explore their diversity and distribution in these insects. We tested the presence of Bartonella spp., Polychromophilus spp.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
(69 reference statements)
1
2
0
1
Order By: Relevance
“…The search for Bartonella in the populations of Rousettus aegyptiacus brought detection of the genotype Candidatus Bartonella rousetti from the bat fly Eucampsipoda africana Theodor, 1955, a frequent ectoparasite of this fruit bat. This strain was found in this bat fly collected in Nigeria (Bai et al 2018 ) and Zambia (Szentiványi et al 2022 ) and was also confirmed in the blood of R . aegyptiacus from Kenya (Kosoy et al 2010 ).…”
Section: Introductionsupporting
confidence: 52%
“…The search for Bartonella in the populations of Rousettus aegyptiacus brought detection of the genotype Candidatus Bartonella rousetti from the bat fly Eucampsipoda africana Theodor, 1955, a frequent ectoparasite of this fruit bat. This strain was found in this bat fly collected in Nigeria (Bai et al 2018 ) and Zambia (Szentiványi et al 2022 ) and was also confirmed in the blood of R . aegyptiacus from Kenya (Kosoy et al 2010 ).…”
Section: Introductionsupporting
confidence: 52%
“…africana flies from R. aegyptiacus (Figures S1-S7; Table S5). This genogroup, identified from cultured isolates as B. rousetti, has been found in R. aegyptiacus sampled to date from Kenya, Nigeria, Zambia, South Africa, and several countries in the Middle East (Kosoy et al, 2010;Bai et al, 2018;Qiu et al, 2020;Szentiványi et al, 2023;Špitalská et al, 2024) was in flies from Príncipe and São Tomé (Figure 4B). No clear evidence of population structure was found in Bartonella genogroups at any of the sequenced markers (ITS, ftsZ, gltA).…”
Section: Patterns Of Bartonella Prevalence and Diversitymentioning
confidence: 67%
“…africana bat flies (Kosoy et al, 2010;Billeter et al, 2012;Kamani et al, 2014;Bai et al, 2015Bai et al, , 2018Qiu et al, 2020;Szentiványi et al, 2023;Špitalská et al, 2024), suggesting that bat flies are vectors of these bacteria. The diversity of bartonellae infecting E. helvum is especially high, including at least six genogroups that meet criteria for recognition as distinct species (Bai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Блохи являются хорошо известными переносчиками возбудителей ряда инфекционных и паразитарных заболеваний человека и животных, среди которых необходимо, в первую очередь, назвать Yersinia pestis van Loghem, 1944 (этиологический агент чумы). Исхнопсиллиды в этом отношении практически не обследованы, а еди-ничные исследования [20,318,376] не позволяют пока говорить о них как о векторах патогенных микроорганизмов.…”
Section: таблица 1 функционально важные химические соединения в соста...unclassified